(3GdNWGH GdfShj h GdhYj HMbhb GdeQCI aj GdeedcI GdYQHjI GdSYhOjI (B: s (3OQGSI MGdI dWGdHGJ GdLGeYI (B= Feminist discourse and awareness of women`s rights in Saudi Arabia : A case study of university students / s - (3efGd YHOGddg GdPjGHs; (3SGej eMeO fUGQ (B: s; (3eMehO MSGf SYjO (B: s ((3GdbGgQI (B: s (3efGd YHOGddg GdPjGH (B: s, 2013)
(3gOaJ GdOQGSI Edi Gdhbha Ydi eOi hYj WGdHGJ GdLGeYGJ GdSYhOjI HMbhb GdeQCI h GdYhGed GdechfI dgPG GdhYj h GdeDKQI ajg (B: (3h hVY JUhQ ebJQM dQaY eSJhi hYj WGdHGJ GdLGeYI GdSYhOjGJ aj eLGd Mbhb GdeQCI aj VhA JhLgGJ GdNWGH GdfShj GdSYhOj (B: (3h JchfJ YjfI GdOQGSI ef (B( 1000) (3WGdHI ef LGeYI Gdedc YHOGdYRjR (B: (3h GSJNOeJ GdHGMKI GdGSJHGfI cCOGI dLeY GdHjGfGJ s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ h GdHMhK GdJQjhjI (B- (3bSe CUhd GdJQHjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdNWGH GdfShjs; (3GdeedcI GdYQHjI GdSYhOjIs; (3GdhYj HMbhb GdeQCIs